Occurrence of Trichomonas vaginalis and Candida spp. infections among married women attending General Brack Hospital and private gynaecology clinics in Brack Al-Shati region, a cross sectional study (Journal of Medical Sciences, 2021)
The focus of the current study was on exploring the epidemiological profiles of Trichomonas vaginalis and Candida spp. infections among married women admitted gynaecology clinics in Brack Al-Shati region. 234 of vaginal swab samples were collected and subjected to direct microscopic examination for microorganisms’ characterization. 45 (19.23%) of overall samples examined were found to be T. vaginalis and Candida spp. positives.  Occurrence of each infection agent was individually compared. Infection with Candida spp were statistically (p= 0.003) raised 32 (13.7%) over that of T. vaginalis infection 13 (5.6%). Co-infections were observed in only 2 (4.4%) of overall positives. No significant associations were observed between these infections and women age categories. Women had history of miscarriages and those had university levels were statistically linked (p